﻿Oral acute toxicity study extract ethanol of balakka fruit (Phyllanthus emblica) - Endy Juli Anto; Rony Abdi Syahputra; Hendrika Andriana Silitonga; Putri Cahaya Situmorang; Sony Eka Nugaraha (Pensoft Publishers, 2022)
Phyllanthus emblica (PE) is a plant widely found in Indonesia, especially in Sumatra island, and in India. This study followed the OECD No. 420. The groups were divided based on gender, male and female rats. Male rats were divided into 6 groups, which were male/female control, male/female 2000 mg/kgBW, and male/female 5000 mg/kgBW. This study revealed that the ethanol extract of Phyllanthus emblica (EEPE) doses of 2000 mg/kgBW and 5000 mg/kgBW did not cause histological changes in the heart, liver, testes, ovaries, and kidneys, and did not cause changes to the hematological parameters, kidney biochemical parameters, liver biochemical parameters, and electrolyte parameters both in male and female rats. The results show that the LD50 of EEPE is higher than 5000 mg/kgBW. In short, this study provides information regarding the antioxidant activity and the safe use of EEPE. The LD50 of extract ethanol of Phyllanthus emblica is higher than 5000 mg/kgBW.